IMPLEMENTASI PEMBERIAN BANTUAN HUKUM BAGI RAKYAT MISKIN DI JAWA TENGAH BERDASARKAN UNDANG-UNDANG NOMOR 16 TAHUN 2011 TENTANG BANTUAN HUKUM - Saefudin, Yusuf (MIH FH UNSOED, 2015)
The establishment of the act of no. 16 years old 2011 about legal aid give new hope to the poor to get access to justice (access to justice) and similarity in to law (equality before the law). This research intend to understand the extent of the implementation of the provision of assistance in central java and the obstacles affecting it in their implementation. The research is the qualitative study with the methods normatif-empiris approach. Data collection is done with the study documents and interviewing people who are considered closely connected with the problems the treatment. The accumulated data analyzed by using analysis of qualitative data. Act of no. 16 years old 2011 about legal aid not implementation well in central java. The factors that hinder there are three, people the substance legal factors , legal structure and cultural law.Â Keyword: Legal Aid, Implementation of legal aid, Poor folk in Central Java, UUBH